Increased populations will be exposed to the dangerous precipitation extremes across China in the future - Xu, Huiwen; Chen, Huopo; Wang, Huijun (Frontiers in Earth Science, 2022)
This study investigates the future changes in dangerous precipitation extremes with multiyear return periods and the population exposure across China at the 1.5-4°C warming levels via the latest simulations from the Coupled Model Intercomparison Project Phase 6 (CMIP6). The results show that the simulations project more frequent dangerous precipitation extremes across China under the warmer climate regardless of the shared socioeconomic pathway (SSP), with more substantial occurrence increases at the high warming levels. Consequently, the population exposure to dangerous precipitation extremes is anticipated to increase persistently in most regions of China except for some parts of northwestern China and the Tibetan Plateau. For the events estimated to occur once every 10 years, the 1.5°C, 2.0°C, 3.0°C, and 4.0°C warming relative to the current state will result in approximately 29.9%, 47.8%, 72.9%, and 84.3% increases in the aggregated population exposure over China under the SSP5-8.5 scenario, respectively. However, the exposure change is somewhat subject to the emission scenarios, with larger proportional increases under the regional-rivalry scenario of SSP3-7.0 compared to the fossil-fueled development scenario of SSP5-8.5. The increased exposure under all the scenarios is primarily attributed to the climate change factor, and the population change and their interaction component make a minor contribution. Furthermore, compared to the 2.0°C warmer climate, the 0.5°C less warming under the 1.5°C climate can trigger remarkable decreases of 16.5%-20.8% for exposure to once-in-decade events over China. Additionally, the changes in the occurrence and exposure are much larger for the rarer events. Hence, our analyses indicate that limiting warming to 1.5°C is beneficial to reducing the impacts associated with precipitation extremes across China, particularly for the more extreme events.